Mood disorders in the elderly: prevalence, functional impact, and management challenges - Valiengo L; Stella F; Forlenza OV (Neuropsychiatric Disease and Treatment)
Leandro da Costa Lane Valiengo,1 Florindo Stella,1,2 Orestes Vicente Forlenza1 1Laboratory of Neuroscience (LIM-27), Department and Institute of Psychiatry, Faculty of Medicine, University of São Paulo, Sao Paulo, 2Biosciences Institute, Universidade Estadual Paulista, Rio Claro, Brazil Abstract: Despite the lower prevalence of severe mood disorders in the elderly as compared to younger adults, late-life depression and bipolar disorder (BD) are more strongly associated with negative outcomes related to the presence of medical comorbidities, cognitive deficits, and increased suicide risk and overall mortality. The mechanisms that contribute to these associations are probably multifactorial, involving pathological factors related directly and indirectly to the disease itself, ranging from biological to psychosocial factors. Most of the accumulated knowledge on the nature of these associations derives from naturalistic and observational studies, and controlled data are still scarce. Nonetheless, there has clearly been a recent growth of the scientific interest on late-life BD and geriatric depression. In the present study, we review the most relevant studies on prevalence, clinical presentation, and cognitive/functional impact of mood disorders in elderly. Several clinical–epidemiological studies were dedicated to the study of the prevalence of mood disorders in old age in distinct settings; however, fewer studies investigated the underlying neurobiological findings and treatment specificities in late-life depression and BD. In the present study, we further discuss the implications of these findings on the management of mood disorders in older adults. Keywords: depression, bipolar disorder, psychogeriatric, geriatric, old age, older adults